Bdellovibrio reynosensis sp. nov., from a Mexico soil sample. Issue 12 (14th December 2022) - Ajao, Yewande Olajumoke; Rodríguez-Luna, Isabel Cristina; Elufisan, Temidayo Oluyomi; Sánchez-Varela, Alejandro; Cortés-Espinosa, Diana Verónica; Camilli, Andrew; Guo, Xianwu
Abstract : A novel predatory bacterium, strain LBG001 T, has been isolated from Reynosa, Mexico. The 16S rRNA shares approximately 97 % sequence identity with many reported strains in the genus Bdellovibrio including the type strain Bdellovibrio bacteriovorus HD100 T . Phylogenetic trees based on the 16S rRNA gene and on 30 concatenated housekeeping genes or core genes showed that LBG001 T is on a separate branch from the B. bacteriovorus group. LBG0001 T has a genome size of 3 582 323 bp with a G+C content of 43.1 mol %. The average nucleotide identity, average amino acid identity and digital DNA–DNA hybridization values with other members of the genus Bdellovibrio (<79, <72 and <17 %, respectively) qualifies the strain to represent a new species in the genus. Strain LBG001 T formed visible plaques on all 10 tested Gram-negative bacterial species. The phenotypic characteristics, phylogenetic analysis and genomic taxonomic studies support the classification of the strain as representing a new species for which the name Bdellovibrio reynosensis sp. nov. is proposed. The type strain is LBG001 T (=ATCC TSD-288 T = CM-CNRG 0932 T ).